Values of Nationalism in the Extracurricular Activity of Boys Scout at Public Elementary School 3 Palu - Aspin, Pipin Yunita; Wasino, Wasino; Yusuf, Amin (Journal of Primary Education)
This study has a purpose of analyzing the implementation of nationalism values, the role of the principal, teachers, scout coaches, and obstacles in the implementation of scouting activities at Public Elementary School 3 Palu. This study was interactive qualitative research. Subjects who participated in the study were the principal, teachers, scoutmaster, and students. This study applied observations, interviews, and documentation for data collection techniques. The data in this study were analyzed using Miles and Huberman interactive models. The results showed that the values ​​of nationalism were formed through the implementation of scouting activities including marching lines, singing national and regional songs, games, rigging, and campsites, The role of the principal and the teacher was to supervise, provide information and participate in a number of scout activities, and the role of the scoutmaster is to familiarize students with fun scouting activities, The obstacles found in its implementation were weather conditions, student activities outside of school as well as facilities and infrastructure.